An overview of the use of dental stem cells and polycaprolactone scaffolds in tissue engineering - ÇALIKOĞLU KOYUNCU, AYŞE CEREN; UZUN, MUHAMMET; GÜNDÜZ, OĞUZHAN (My University, 2021)
Dental tissues have been discovered as a pool of stem cells with multiple differentiation potencies in recent decades. Stem cells with different differentiation potential, but particularly of mesenchymal origin, could easily be isolated from dental pulp, periodontal ligament, apical papilla, dental follicle, and gingiva, as well as the exfoliated deciduous teeth and third molar teeth germs. Polycaprolactone is a well-known biomaterial that has been used in the engineering of many tissues for more than 30 years because of its excellent tailorability and availability. This chapter will review the types of dental stem cells, techniques in producing polycaprolactone scaffolds, and different tissue engineering applications involving dental stem cells and polycaprolactone.
Keywords: Dental stem cells; Polycaprolactone; Scaffold manufacturing; Tissue engineering